Decadal Changes in Seabird Foraging Activity, Forage Fish, and Plankton in Cattle Pass, San Juan Islands, Washington - Runnells, Emily S. (My University, 2014)
Published and unpublished reports suggest that seabird numbers have decreased markedly in the Salish Sea over the past several decades. I tested the hypothesis that seabird feeding activity in a known foraging location decreased in 2010 and 2011 in comparison to the mid-1990s, and that this decrease was associated with a concomitant decrease in the abundance of small, pelagic fish, and changes in the plankton community. Data collection replicated methods used in the mid-1990s, including land-based surveys of seabird foraging aggregations, acoustic surveys to determine the distribution and abundance of fish, and vertical plankton tows. I found significant decreases in seabird foraging activity between decades, as well as a decrease in area integrated backscatter (a measure of fish abundance), and calanoid copepod abundance. This demonstrates that well-placed assessments can detect differences in three trophic levels of the Salish Sea community in a way that can inform ecosystem-based management.
Thesis (Master's)--University of Washington, 2014
Keywords: Decadal change; Forage fish; Foraging flocks; Salish Sea; Trophic; Ecology; Biological oceanography; fisheries